Impact of heat and high-moisture pH treatments on starch digestibility, phenolic composition, and cell bioactivity in sorghum (Sorghum bicolor L. Moench) flour - Peterson, Jaymi; Santana, Adina L.; Cox, Sarah; Perez-Fajardo, Mayra; Covarrubias, Jose; Perumal, Ramasamy; Bean, Scott; Wu, Xiaorong; Wang, Weiqun; Smolensky, Dmitriy (Frontiers in Nutrition, 2024)
Sorghum (Sorghum bicolor L. Moench), characterized by substantial genetic diversity, encompasses some lines rich in health-promoting polyphenols. Laboratory studies have demonstrated anticancer properties of sorghum phenolics; however, their presence may impact nutritional factors, such as digestible starch. The objective of this study was to determine the effects of pH and high-moisture heating on starch digestibility, phenolic profile, and anticancer activity in sorghum. High Phenolic sorghum flour line SC84 was combined with buffer solutions (pH 3, 4, 5, 7, and 8) and heated for 0, 10, 30, 60, or 120 min. Starch digestibility was assessed using the K-DSTRS kit from Megazyme. Changes in phenolic composition were analyzed using total phenolic content (TPC) and condensed tannin content (CTC) assays coupled with reversed phase high performance liquid chromatography (RP-HPLC) analysis. Anticancer potential against human colorectal cancer cells (HCT116 and SW480) was determined though cell viability assay. Results indicated a significant increase in total starch digestibility of sample after heating. Heating samples for 10 min did not significantly reduce TPC of samples. However, CTC was significantly reduced with heating time, while pH exhibited no significant effect on CTC. The measured 3-deoxyanthocyanidins experienced a significant decrease (p < 0.0001), while certain flavonoids increased significantly (p < 0.05) after heating for 30 min or longer. Notably, the 10 min heating duration minimally affected anticancer activity, whereas longer heat times diminished extract efficacy against human colorectal cancer cells. Alkaline pH levels significantly decreased anticancer activity, regardless of heating time. Importantly, heating sorghum for 10 min improved starch digestibility with minimal compromise to potential health benefits. These findings suggest promising implications for the development of high-phenolic sorghum products, and provide valuable insights to guide forthcoming animal and clinical studies. The demonstrated impact of wet-heating on increased starch digestibility, coupled with the preservation of phenolic content and bioactivity, underscores the potential of incorporating high-phenolic sorghum lines in future functional food formulations.